Absence as Presence, Presence as Absence: Museological Storytelling in Berlin - Parker, Joshua (Narrative Works)

(untitled) (Centre for Interdisciplinary Research on Narrative, St. Thomas University, 2013)
This article examines a long history of objects’ use in “telling stories,” and speculates on how museums and other art forms might encourage “narrations” while leaving story-telling to visitors or viewers. David Chipperfield’s 2009 “restoration” of Berlin’s Neues Museum made great efforts to preserve traces not only of the objects displayed inside, but to present an open-ended “narrative” of the building’s own history. Attempts at making historical sites “tell” stories have, meanwhile, also extended into other visual arts in Germany, of which the article examines several, discussing them in relation with the concept of “postmemory” and national narratives of identity.